Employment and Earning Gaps in the Early Career of Ethnic Minority British Graduates: the Importance of University Choice, Parental Background and Area Characteristics - Wouter Zwysen; Simonetta Longhi (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2016)
We compare employment and earnings of British graduates belonging to ethnic minorities to those of white British six months and three and a half years after graduation. Six months after graduation all ethnic minority graduates are less likely than whites to be employed but those who have a job earn similarly or more than whites. University choice, parental background and area characteristics account for a large part of the ethnic differences in earnings but do not explain ethnic differences in employment. Three and a half years after graduation the ethnic advantages in earnings disappear while employment penalties reduce. Both employment probability and earnings increase over the career in a similar way for whites and minorities, with only few exceptions.
Keywords: I24; J15; R23; 330; School-to-work transitions; graduates; ethnic gaps; UK; longitudinal analysis